2020
DOI: 10.1097/brs.0000000000003374
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Predictors of Better Long-term Functional Ability and Decreased Pain Following LSS Surgery

Abstract: Study design A prospective observational 10-year follow-up studyObjective This study aimed to examine preoperative predictors for better surgical outcomes in patients with lumbar spinal stenosis (LSS) 10 years after surgery. Summary of Background DataLSS is a leading cause of low back surgery in patients older than 65 years. Limited data is available for predictors of long-term surgical outcomes in patients with LSS. Methods At the baseline, 102 patients with LSS underwent decompressive surgery, and 72 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It is currently reported that most studies reporting the postoperative clinical effects of LSS are focused on improving postoperative radiative pain, whereas few studies report improvements in postoperative numbness [25][26][27][28][29]. Typically, patients experience significant pain relief after lumbar decompression surgery, but the sensation of numbness does not improve as much as they might expect.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently reported that most studies reporting the postoperative clinical effects of LSS are focused on improving postoperative radiative pain, whereas few studies report improvements in postoperative numbness [25][26][27][28][29]. Typically, patients experience significant pain relief after lumbar decompression surgery, but the sensation of numbness does not improve as much as they might expect.…”
Section: Discussionmentioning
confidence: 99%
“…According to past studies, patients tend to have more optimistic expectations for postoperative symptom improvement rather than the actual surgical outcome [9] and often expect their symptoms to be completely resolved after surgery [10]. However, even after spinal surgery, some degree of pain and functional impairment remain, and some patients experience adverse events [23][24][25]. This disjunction between expectations and reality can be explained as a result of the lack of information given to the patients.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Though MIS-TLIF has only been in use for a relatively short period, it has demonstrated comparable, and sometimes superior, surgical outcomes compared to traditional open surgery. It offers advantages such as reduced trauma and fewer complications [17,18]. MIS-TLIF creates an expandable traction channel through a small incision, preserving the posterior ligament complex (PLC) structure, thus maximizing posterior structural stability [19].…”
Section: Correlation Analysis Between the Postoperative Changes In Th...mentioning
confidence: 99%